Perancangan Sistem Pengelolaan Limbah Cair Industri Tempe di Desa Bandungrejo –Kecamatan Mranggen – Kab. Demak - Joko, Tri; Sulistiyani, Sulistiyani; Setyaningsih, Yuliani (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2003)
ABSTRACT Background : Problems which often appear in small industrial environment especially from the central industry of tempe is lack of awareness of society in management of the environment It is associated with the limited fund to build waste water facility and also its operating expenses. The Central Industry of tempe in Bandungrejo District of Mranggen at this time. The amount of is 26 home industries of tempe product are marketed to the region of Demak and its surroundings, amount to and also to region part of east town of Semarang. For the efficacy of product of tempe, waste also generate problem especially related to contamination of ground water, decrease quality of wells, dig water as the source of clean. Method : To overcome the mentioned hence, it requires a cheap waste water treatment system design, easy to operate and also with economized energy. Result : As conclusion of this research is that source of waste water of tempe industry comes from washing process, poaching of seed process, soaking and resolving of soy husk and seed process, debit/capacities waste water of tempe mean equal to 1,27 m3/day/industry, waste water characteristic of tempe Industry has the character of organic with comparison of BOD/COD = 0,4 - 0,5, the proposed of IPAL design is by using batch system through anaerobic system with usage of PVC pipe media of wasp den at biofilter process. Suggested from results of this research are the importance of giving knowledge to society of central industry of tempe about tere impacts to the environment by activity making of tempe and also the importance of forming and stabilization of organization management of industrial waste water so that reaching of continuity of operation and maintenance of WWTP (Waste Water Treatment Plan). Key words : anaerobic biofilter, industrial waste water of tempe